Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
M. L. Perkins, Theme and form in Voltaire's alphaetical works Jeanne R. Monty, Voltaire's rhetoric: the use of written evidence in the alphabetical works Theodore Besterman, Voltaire bibliography: the impossible dream Young Hai Park, La Carrière scénique de L'Orphelin de la Chine Daniel S. Hawley, L'Inde de Voltaire Barbara Widenor Maggs, Answers from eighteenth-century China to certain questions on Voltaire's sinology Arnold Ages, Voltaire and Horace: the testimony of the correspondence Irwin L. Greenberg, Destination in Jacques le fataliste Anna Attridge, The Reception of La Nouvelle Héloïse Irving Wohlfarth, The Irony of criticism and the criticism of irony: a study of Laclos criticism James F. Jones, Jr, Visual communication in Les Egarements du cœur et de l'esprit Elizabeth Anderson, La Collaboration de Sonnini de Manoncourt à l'Histoire naturelle de Buffon